2007
DOI: 10.1126/science.1146853
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Toxicity Tolerance in Barley Arising from Efflux Transporter Amplification

Abstract: Both limiting and toxic soil concentrations of the essential micronutrient boron represent major limitations to crop production worldwide. We identified Bot1, a BOR1 ortholog, as the gene responsible for the superior boron-toxicity tolerance of the Algerian barley landrace Sahara 3771 (Sahara). Bot1 was located at the tolerance locus by high-resolution mapping. Compared to intolerant genotypes, Sahara contains about four times as many Bot1 gene copies, produces substantially more Bot1 transcript, and encodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
343
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 414 publications
(361 citation statements)
references
References 17 publications
13
343
2
3
Order By: Relevance
“…The first B toxicity tolerance gene identified in plants was the barley 4H QTL gene Boron tolerance 1, Bot1 (Reid 2007, named as such by Sutton et al 2007 following the accepted rules for nomenclature and gene symbolization in barley (Franckowiak et al 1997). Bot1 was identified using an approach combining positional cloning and reverse genetics.…”
Section: B Tolerance In Barleymentioning
confidence: 99%
“…The first B toxicity tolerance gene identified in plants was the barley 4H QTL gene Boron tolerance 1, Bot1 (Reid 2007, named as such by Sutton et al 2007 following the accepted rules for nomenclature and gene symbolization in barley (Franckowiak et al 1997). Bot1 was identified using an approach combining positional cloning and reverse genetics.…”
Section: B Tolerance In Barleymentioning
confidence: 99%
“…In particular, the entire chromosome-level collinearity was observed between barley chromosome 3H and rice chromosome 1 (Figure 4). Comparative genomic information can aid systematic marker generation even when the corresponding interval in the rice genome lacks a barley ortholog (Komatsuda et al, 2007;Sutton et al, 2007). This approach is particularly useful for the identification of functional homologs in both species (Inukai et al, 2006) and identification of candidate orthologs in barley.…”
Section: K Sato Et Almentioning
confidence: 99%
“…The size of a sliding window was chosen to include 30 adjacent positions in the genetic map. Yan et al, 2006;Komatsuda et al, 2007;Sutton et al, 2007;Taketa et al, 2008;Nair et al, 2010;Ramsay et al, 2011) were searched for the presence of flanking or cosegregating markers and gene sequences with BLASTN (Altschul et al, 1990), or BAC clone identifiers from the original publications were identified in the FPC database of fingerprinted contigs.…”
Section: Distribution Of Bac Librariesmentioning
confidence: 99%